Nurse's Psychological Experiences of Caring for Severe COVID-19 Patients in Intensive Care Units: A Qualitative Meta-Synthesis - Han, Peng; Duan, Xia; Zhao, Sijia; Zhu, Xiaoping; Jiang, Jinxia (Frontiers in Public Health, 2022)
Background COVID-19 has been listed as an international public health emergency. During the pandemic, the nurses were affected physically and mentally when in contact with and caring for patients infected with COVID-19, especially those in intensive care units (ICUs). Objective To summarize and evaluate the actual psychological experience of nurses caring for patients with severe pneumonia in the ICUs during the COVID-19 pandemic. Methods Relevant publications were identified by systematic searches across 11 databases in December 2021. All qualitative and mixed-method studies in English and Chinese from 2019 that explored the experiences of nurses who cared for severe COVID-19 patients in ICUs were included. The qualitative meta-synthesis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Two independent reviewers selected the studies and assessed the quality of each study. Meta-synthesis was performed to integrate the results. Results A total of 12 studies revealed 9 sub-themes and 3 descriptive themes: physical reactions and psychological changes, the need for support from multiple sources, and increased adaptation and resilience. Conclusion Nurses who treated severe COVID-19 patients have experienced severe work trials and emotional reactions during the pandemic. They have also developed personally in this process. Managers should develop strategies that address the nurses’ needs for external support, reasonably respond to public health emergencies, and improve nursing care outcomes.